Electrical properties of zinc tellurite glasses doped with europium oxide [electronic resource] - Noor Fadhilah Muhamad Sahapini, 1984-; Fakulti Sains (2008)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2008